Toll-Like Receptor 4 Gene Polymorphisms and Susceptibility to Schizophrenia: A Case-Control Study. (3rd October 2022) - Mostafa, Maged; Elwasify, Mohamed; Fathy, Aya Ahmed; Abdelsalam, Maha
ABSTRACT: Schizophrenia is a common psychiatric disorder that exhibits a variety of symptoms. The exact etiology and pathogenesis are still doubtful. However, genetic and environmental factors seem to have a role. Years ago, the role of the immune system was focused on auto-antibodies, cytokines, different types of immune cells and immune genes. The Toll-like receptors (TLR) are a cornerstone of the innate immune system, particularly TLR4. TLR4 primarily recognises gram-negative lipopolysaccharides bacteria. This case-control study, for the first time to our knowledge, examined the role of TLR4 gene polymorphisms in 142 Egyptian schizophrenic patients and 175 healthy controls. Using polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP), four single nucleotide polymorphisms (SNPs) were investigated in the TLR4 gene rs11536889, rs10759931, rs1927911, and rs1927914. The Positive and Negative Syndrome Scale (PANSS) was used in diagnosis and assessment. A statistically significant association was observed between rs11536889, rs1927911 and rs1927914, but no association was found between rs10759931. There was no association between the different SNP genotypes and PANSS, except between rs1927914 and general psychopathologic symptoms. This study shows a strong association between TLR4 rs11356889 and rs1927911 minor alleles and schizophrenia. These findings could be additional evidence for the immune system's role in schizophrenia development. However, more studies with a more significant sample number, TLR4 protein assessment, and a larger number of SNPs are recommended.